PELATIHAN MICROSOFT OFFICE 2010 PADA K3TK DAN GUGUS PAUD NAGA DI KOTA BATAM - Rika Harman; Tukino Tukino; Amrizal Amrizal; Sasa Ani Arnomo (ASOSIASI IDEBAHASA KEPRI, 2022)
The material provided in this training is divided into 3 groups, namely Microsoft Word 2010, Microsoft PowerPoint 2013, and Microsoft Paint groups. The briefing material given to the Microsoft PowerPoint 2010 group was the introduction of spreadsheets, starting from worksheets, to the use of functions and formulas to solve problems. Activities are carried out based on the division of the ability/skill level of each teacher. Teachers who have been proficient are grouped separately from teachers who are still new to computers so that coaching is more intensive. Teachers who are still laymen are guided and accompanied by instructors starting from the procedure for turning on the computer, opening files, saving files, using the mouse, basic typing, introduction to computer parts to the procedure for turning off the computer. The introduction to the spread sheet material begins with explaining worksheets, menu functions, and how to create borders, introducing cell alignment, and introducing Microsoft Excel formulas and functions to solve a particular problem/case. So far we have known more or less about Microsoft Office, including Microsoft Office XP, Microsoft Office 2003, Microsoft Office 2007, and the latest we know is Microsoft Office 2010.